Implementation of Fisher Yates Algorithm for Question Randomization in Human Digestive System Educational Application - Mughits, Muhammad Choirul; Krisdiawan, Rio Andriyat; Herwanto, Heri (JURNAL SISFOTEK GLOBAL, 2025)
At SMPN 1 Lebakwangi, the teaching and learning process of science subjects in class VIII has utilized media such as books and videos, with identical exercises and quizzes given to all students. However, this approach faces challenges due to the limited variety of learning media and practice questions, which rely heavily on textbooks. As a result, students often struggle to absorb and understand the material effectively, finding the learning process less interesting and diverse. This research aims to develop alternative learning media in the form of an educational application that focuses on the human digestive system. The app incorporates the Fisher-Yates algorithm to randomize quiz questions, ensuring that students receive different sequences of questions. The system was developed using RUP (Rational Unified Process) methodology, and the design was made with UML (Unified Modeling Language). User Acceptance Test (UAT) results show the effectiveness of the application, with scores of 91.66% for appearance, 92.47% for material content, 89.74% for learning process, and 91.77% for improving understanding. This educational app serves as an interactive, engaging, and diverse learning medium, offering alternative practice questions that improve understanding of human digestive system material.